Improving R&D decisions and execution - Menke, Michael M.
Michael M. Menke describes tools that create value for an organizing by setting priorities for allocating R&D resources and supporting smart execution of projects.
A set of quality tools is designed to help project teams to collaborate more efficiently and effectively.
Decision quality and execution quality in R&D are very different, but both can be improved by using a common set of quality tools. These tools, including strategy tables, influence diagrams, sensitivity analysis, decision trees, and portfolio grids, have evolved from the decision quality movement and complement the quality tools from TQM. These tools are especially useful for companies that want to manage R&D explicitly to create shareholder value.
Keywords: R&D.